Integrasi Konsep Amanah dalam Shariah Enterprise Theory: Tinjauan Literatur Komprehensif - M, Riska Amalia; Lince Bulutoding; Sumarlin (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
This study presents a comprehensive review of the integration of the concept of trust in Shariah Enterprise Theory (SET) in the context of Sharia-based business. Using library research methods, this article analyzes various literature sources related to the concept of trust in SET, with a focus on Sharia principles that prioritize transparency, justice and business ethics. The results of the analysis show that the concept of trust plays a crucial role in ensuring integrity and trust in Sharia-based business operations. SET was born from the belief in the Oneness of Allah and the interconnectedness of humans as caliphs in resource management. The distribution of wealth or added value in SET does not only apply to participants directly involved, but also to parties involved indirectly, reflecting the principles of justice and equality in Islam. SET also proposed the concept of disclosing social responsibility and linking it to the principle of trust, emphasizing the importance of transparency, accountability and sustainability in Sharia-based business operations. By understanding the roles and responsibilities of various parties, SET promotes the principle of trust in Sharia business management, creating an ethical, fair and sustainable business environment in accordance with Islamic values.